Effects of lycopene on oxidative stress and remnant liver histology after partial hepatectomy in rats - Ayan, Fadil; Aytac, Erman; Saygili, Seha; Genc, Habibe; Karaca, Cetin; Bayrak, Ibrahim; Uzun, Hafize; Salihoglu, Ziya; Erdamar, Sibel; Sozer, Volkan; Altug, Tuncay; Seymen, Pinar; et al. (TURKISH SOC GASTROENTEROLOGY, 2011)
Background/aims: Partial hepatectomy is performed for the treatment of mass lesions in the liver. Lycopene, which is a carotenoid, is present in various physiologic processes. In this study, the effects of lycopene administration in partially hepatectomized rats were evaluated by assessing various oxidant/antioxidant parameters, remnant liver histology and plasma nitric oxide levels. Methods: Thirty Wistar albino adult male rats were randomly divided into three equal groups as: Sham, Partial Hepatectomy and Lycopene-Administered + Partial Hepatectomy groups. Lycopene (4 mg/kg), which was dissolved in olive oil, was given to the rats per orally (via gavage tube) (0.1 ml) every day for 6 weeks before partial hepatectomy and for one week after partial hepatectomy. Tissue and blood samples were collected one week after partial hepatectomy. Results: Plasma malondialdehyde (p < 0.001) and nitric oxide (p < 0.05) levels in the lycopene-administered + partial hepatectomy group were significantly higher than in the partial hepatectomy group. Intraerythrocytic glutathione (p < 0.001), plasma (p < 0.001) and liver tissue Cu-Zn (p < 0.05) superoxide dismutase levels of the lycopene-administered + partial hepatectomy group were significantly lower than in the partial hepatectomy group. Conclusions:,Lycopene administration could be harmful by increasing oxidative stress after partial hepatectomy.
Keywords: Partial hepatectomy; oxidative stress; lycopene; nitric oxide; NITRIC-OXIDE RELEASE; LIPID-PEROXIDATION; VITAMIN-E; REGENERATION; CAROTENOIDS; METASTASES; HEPATOCYTE; RESECTION; GROWTH; INJURY; Gastroenterology & Hepatology